2020
DOI: 10.3390/s20092493
|View full text |Cite
|
Sign up to set email alerts
|

Integrating SIF and Clearness Index to Improve Maize GPP Estimation Using Continuous Tower-Based Observations

Abstract: Solar-induced chlorophyll fluorescence (SIF) has been proven to be well correlated with vegetation photosynthesis. Although multiple studies have found that SIF demonstrates a strong correlation with gross primary production (GPP), SIF-based GPP estimation at different temporal scales has not been well explored. In this study, we aimed to investigate the quality of GPP estimates produced using the far-red SIF retrieved at 760 nm (SIF760) based on continuous tower-based observations of a maize field made during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 79 publications
4
11
1
Order By: Relevance
“…SIF and GPP linear regression was larger on cloudy days that exhibit a higher proportion of diffuse PAR, which is consistent with findings for maize [21], rice paddy [19], and mixed broad-leaved forest [49]. Middle and lower parts of the canopy can receive more radiation under cloudy conditions [5,47], enabling the middle and lower canopy to participate in SIF emission and photosynthesis. However, the influence of measurement techniques must be taken into account in that tower-based spectrometers will predominantly receive the SIF signal that was emitted from the top canopy leaves and escaped from the inside canopy [57,58], meanwhile, GPP divided from EC measurements comes from a larger area, and the carbon released by the internal leaves will eventually escape from the canopy [59].…”
Section: The Sif-gpp Relationship On Different Timescalessupporting
confidence: 85%
See 2 more Smart Citations
“…SIF and GPP linear regression was larger on cloudy days that exhibit a higher proportion of diffuse PAR, which is consistent with findings for maize [21], rice paddy [19], and mixed broad-leaved forest [49]. Middle and lower parts of the canopy can receive more radiation under cloudy conditions [5,47], enabling the middle and lower canopy to participate in SIF emission and photosynthesis. However, the influence of measurement techniques must be taken into account in that tower-based spectrometers will predominantly receive the SIF signal that was emitted from the top canopy leaves and escaped from the inside canopy [57,58], meanwhile, GPP divided from EC measurements comes from a larger area, and the carbon released by the internal leaves will eventually escape from the canopy [59].…”
Section: The Sif-gpp Relationship On Different Timescalessupporting
confidence: 85%
“…In addition, this study has inconsistent results with previous studies [21,47] and possible explanations are given in the following analysis. We found that with the aggregation of timescales, the correlation of SIF-GPP deteriorated.…”
Section: The Sif-gpp Relationship On Different Timescalescontrasting
confidence: 76%
See 1 more Smart Citation
“…The seasonal trend in SIF at the Niwot Ridge site, where the majority of the forest consisted of needleaved evergreens, was investigated using both continuous TanSat and tower-based SIF measurements made by Magney et al [76], and also compared with the tower-based NDVI observations, as illustrated in Figure 10. Here, we used the daily mean clearness index (CI) (only CI > 0.6 was used) to determine whether it was clear skies [77]. We calculated the daily SIF under clear-sky conditions, if there are more than three samples a day.…”
Section: Importance Of Solar Radiation Intensity For Better Sif Modellingmentioning
confidence: 99%
“…At sub-diurnal or half-hourly timescales, GPP:SIF was reported to follow an asymptotic trend (Li et al, 2018a;Chen et al, 2020). Indeed, GPP saturates at high APAR, while SIF keeps increasing as APAR increases, leading to a hyperbolic relationship between SIF and GPP at the instantaneous timescale (Damm et al, 2015;Gu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%